2000
DOI: 10.4049/jimmunol.164.10.5146
|View full text |Cite
|
Sign up to set email alerts
|

Human Vascular Endothelial Cells Stimulate Memory But Not Naive CD8+ T Cells to Differentiate into CTL Retaining an Early Activation Phenotype

Abstract: Endothelial cell (EC)-selective alloreactive CTL may mediate alloimmune vascular injury. In the present study, EC-selective CTL were generated in cocultures of purified human CD8+ T cells with allogeneic EC and were compared with conventional CTL against corresponding B lymphoblastoid cells (BLC). EC caused activation and expansion of memory but not naive CD8+ T cells, which differentiated into EC-selective CTL that retained high surface expression of CD69, CD25, and CD62L and displayed low intracellular perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 45 publications
4
67
0
Order By: Relevance
“…The need for exogenously added BOEC is underscored by the observation that the contribution of endogenous EC precursors is insignificant during wound vascularization [45]. Although allogeneic BOEC are more easily available, they have the capacity to initiate an immune response by resting allogeneic T-lymphocytes [46], necessitating the use of autologous BOEC. Autologous fibroblasts may however also be advantageous over allogeneic sources, since the latter were documented to increase scar formation and wound contraction [47].…”
Section: Discussionmentioning
confidence: 99%
“…The need for exogenously added BOEC is underscored by the observation that the contribution of endogenous EC precursors is insignificant during wound vascularization [45]. Although allogeneic BOEC are more easily available, they have the capacity to initiate an immune response by resting allogeneic T-lymphocytes [46], necessitating the use of autologous BOEC. Autologous fibroblasts may however also be advantageous over allogeneic sources, since the latter were documented to increase scar formation and wound contraction [47].…”
Section: Discussionmentioning
confidence: 99%
“…The allogeneic response of CD8 T cells to human EC is mediated mainly by memory T cells and is characterized by T cell proliferation and the sustained expression of CD69 and HLA-DR (14). Dual-color flow cytometry indicated that all iNOS-expressing cells were CD8-positive.…”
Section: Ec Induce Inos Expression In Primarymentioning
confidence: 99%
“…CFSE Labeling and Cell Sorting. T cells were labeled with 1 M CFSE (Molecular Probes, Carlsbad, CA) before coculture with EC as described in SI Materials and Methods and either FACS sorted or analyzed as described previously (14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report showed that the immune response against the transgene can be avoided by use of a liver-specific promoter (17). Since ECs perform poorly as APCs (18,19), we examined gene expression under the control of the PPE-1-3x promoter to see if it would reduce the humoral response against the transgene and increase transgene stability.…”
Section: Introductionmentioning
confidence: 99%